2017
DOI: 10.1007/s00153-017-0581-4
|View full text |Cite
|
Sign up to set email alerts
|

The tree property at the successor of a singular limit of measurable cardinals

Abstract: Abstract. Assume λ is a singular limit of η supercompact cardinals, where η ≤ λ is a limit ordinal. We present two forcing methods for making λ + the successor of the limit of the first η measurable cardinals while the tree property holding at λ + . The first method is then used to get, from the same assumptions, tree property at ℵ η 2 +1 with the failure of SCH at ℵ η 2 . This extends results of Neeman and Sinapova. The second method is also used to get tree property at successor of an arbitrary singular card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Building off techniques of Neeman [13], Sinapova [15] showed that the tree property could consistently hold at the successor of a singular cardinal of any cofinality (along with the failure of SCH). Golshani [6] further refined this result, showing that the tree property could hold at ℵ γ+1 for any limit ordinal γ. Neeman [14] was able to combine the techniques for obtaining the tree property at successors of regular cardinals and successors of singular cardinals, producing a model in which the tree property holds at ℵ n for 2 ≤ n < ω and at ℵ ω+1 simultaneously.…”
Section: Introductionmentioning
confidence: 82%
“…Building off techniques of Neeman [13], Sinapova [15] showed that the tree property could consistently hold at the successor of a singular cardinal of any cofinality (along with the failure of SCH). Golshani [6] further refined this result, showing that the tree property could hold at ℵ γ+1 for any limit ordinal γ. Neeman [14] was able to combine the techniques for obtaining the tree property at successors of regular cardinals and successors of singular cardinals, producing a model in which the tree property holds at ℵ n for 2 ≤ n < ω and at ℵ ω+1 simultaneously.…”
Section: Introductionmentioning
confidence: 82%